Self-management of fatigue in rheumatoid arthritis: a randomised controlled trial of group cognitive-behavioural therapy. Issue 6 (2nd May 2011) - Hewlett, Sarah; Ambler, Nick; Almeida, Celia; Cliss, Alena; Hammond, Alison; Kitchen, Karen; Knops, Bev; Pope, Denise; Spears, Melissa; Swinkels, Annette; Pollock, Jon
Abstract : Objectives: To investigate the effect of group cognitive behavioural therapy (CBT) for fatigue self-management, compared with groups receiving fatigue information alone, on fatigue impact among people with rheumatoid arthritis (RA). Methods: Two-arm, parallel randomised controlled trial in adults with RA, fatigue ≥6/10 (Visual Analogue Scale (VAS) 0–10, high bad) and no recent change in RA medication. Group CBT for fatigue self-management comprised six (weekly) 2 h sessions, and consolidation session (week 14). Control participants received fatigue self-management information in a 1 h didactic group session. Primary outcome at 18 weeks was the impact of fatigue measured using two methods (Multi-dimensional Assessment of Fatigue (MAF) 0–50; VAS 0–10), analysed using intention-to-treat analysis of covariance with multivariable regression models. Results: Of 168 participants randomised, 41 withdrew before entry and 127 participated. There were no major baseline differences between the 65 CBT and 62 control participants. At 18 weeks CBT participants reported better scores than control participants for fatigue impact: MAF 28.99 versus 23.99 (adjusted difference −5.48, 95% CI −9.50 to −1.46, p=0.008); VAS 5.99 versus 4.26 (adjusted difference −1.95, 95% CI −2.99 to −0.90, p<0.001). Standardised effect sizes for fatigue impact were MAF 0.59 (95% CI 0.15 to 1.03) and VAS 0.77 (95% CI 0.33 to 1.21), both in favour of CBT. Secondary outcomes of perceived fatigue severity, coping, disability, depression, helplessness, self-efficacy and sleep were also better in CBT participants. Conclusions: Group CBT for fatigue self-management in RA improves fatigue impact, coping and perceived severity, and well-being. Trial registration: ISRCTN 32195100